The 4.1B cytoskeletal protein regulates the domain organization and sheath thickness of myelinated axons. Issue 2 (26th October 2012) - Einheber, Steven; Meng, Xiaosong; Rubin, Marina; Lam, Isabel; Mohandas, Narla; An, Xiuli; Shrager, Peter; Kissil, Joseph; Maurel, Patrice; Salzer, James L.
Abstract Myelinated axons are organized into specialized domains critical to their function in saltatory conduction, i.e., nodes, paranodes, juxtaparanodes, and internodes. Here, we describe the distribution and role of the 4.1B protein in this organization. 4.1B is expressed by neurons, and at lower levels by Schwann cells, which also robustly express 4.1G. Immunofluorescence and immuno‐EM demonstrates 4.1B is expressed subjacent to the axon membrane in all domains except the nodes. Mice deficient in 4.1B have preserved paranodes, based on marker staining and EM in contrast to the juxtaparanodes, which are substantially affected in both the PNS and CNS. The juxtaparanodal defect is evident in developing and adult nerves and is neuron‐autonomous based on myelinating cocultures in which wt Schwann cells were grown with 4.1B‐deficient neurons. Despite the juxtaparanodal defect, nerve conduction velocity is unaffected. Preservation of paranodal markers in 4.1B deficient mice is associated with, but not dependent on an increase of 4.1R at the axonal paranodes. Loss of 4.1B in the axon is also associated with reduced levels of the internodal proteins, Necl‐1 and Necl‐2, and of alpha‐2 spectrin. Mutant nerves are modestly hypermyelinated and have increased numbers of Schmidt‐Lanterman incisures, increased expression of 4.1G, and express a residual, truncated isoform of 4.1B. These results demonstrate that 4.1B is a key cytoskeletal scaffold for axonal adhesion molecules expressed in the juxtaparanodal and internodal domains that unexpectedly regulates myelin sheath thickness. © 2012 Wiley Periodicals, Inc.